2003
DOI: 10.1042/bst0310920
|View full text |Cite
|
Sign up to set email alerts
|

Sarcolemma agonist-induced interactions between InsP3 and ryanodine receptors in Ca2+ oscillations and waves in smooth muscle

Abstract: Smooth muscle cells respond to InsP(3)-generating (sarcolemma-acting) neurotransmitters and hormones by releasing Ca(2+) from the internal store. However, the release of Ca(2+) does not occur uniformly throughout the cytoplasm but often into a localized area before being transmitted to other regions of the cell in the form of Ca(2+) waves and oscillations to actively spread information within and between cells. Yet, despite their significance, our understanding of the generation of oscillations to waves is inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 65 publications
(88 reference statements)
1
27
0
Order By: Relevance
“…CCh-induced initial Ca 2+ mobilization has been recognized as a result of Ca 2+ release from internal stores, because those are essentially unaffected by removal of extracellular Ca 2+ , and those are not observed by store depletion using thapsigargin or cyclopiazonic acid (CPA), SERCA inhibitors [3]. We found that caffeine blocked lower CCh- ]i rise is blocked by RyR antagonist [8,29]. Caffeine increases both the open time and open probability of RyR in a cooperative manner with both Ca 2+ and ATP, and therefore enhances the affinity of RyR for the physiological activator [30].…”
Section: Discussionmentioning
confidence: 68%
“…CCh-induced initial Ca 2+ mobilization has been recognized as a result of Ca 2+ release from internal stores, because those are essentially unaffected by removal of extracellular Ca 2+ , and those are not observed by store depletion using thapsigargin or cyclopiazonic acid (CPA), SERCA inhibitors [3]. We found that caffeine blocked lower CCh- ]i rise is blocked by RyR antagonist [8,29]. Caffeine increases both the open time and open probability of RyR in a cooperative manner with both Ca 2+ and ATP, and therefore enhances the affinity of RyR for the physiological activator [30].…”
Section: Discussionmentioning
confidence: 68%
“…Findings in Figure 3 showed that RGD but not the control RAD peptide lowered MLC 20 phosphorylation in pressurized cerebral arteries. It also showed that in RGDtreated arteries, the subsequent application of diltiazem but not ryanodine (an SR-depleting agent) further reduced MLC 20 phosphorylation. This finding is consistent with α v β 3 integrin driving this key phosphorylation step through Ca 2+ wave suppression rather than through substantive changes in L-type Ca 2+ channel activity.…”
Section: Discussionmentioning
confidence: 91%
“…Exposing RGD-treated arteries to diltiazem further reduced pressure-induced MLC 20 phosphorylation, whereas ryanodine application had no effect. The latter observation is consistent with α v β 3 integrin signaling directing the phosphorylation of this key contractile protein through Ca 2+ wave generation.…”
Section: Waves and Mlc 20 Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…A feedback between Ca 2+ mobilisation and Ca 2+ -activated and Ca 2+ -inhibited processes can cause [Ca 2+ ] i oscillations in widely different cells [62][63][64][65][66][67][68][69]. This could encompass, e.g., phospholipase C and Ca 2+ -inhibited Ca 2+ release via InsP 3 receptors.…”
Section: How Would Ca 2+ Oscillations Be Produced?mentioning
confidence: 99%